Long-Term Outcome of Chest Wall and Diaphragm Repair with Biological Materials - Merhej, Hayan; Ali, Mohammed; Nakagiri, Tomoyuki; Zinne, Norman; Selman, Alaa; Golpon, Heiko; Goecke, Tobias; Zardo, Patrick (The Thoracic and Cardiovascular Surgeon, 2023)
Introduction Chest wall and/or diaphragm reconstruction aims to preserve, restore, or improve respiratory function; conserve anatomical cavities; and upkeep postural and upper extremity support. This can be achieved by utilizing a wide range of different grafts made of synthetic, biological, autologous, or bioartificial materials. We aim to review our experience with decellularized bovine pericardium as graft in the past decade.Patients and Methods We conducted a retrospective analysis of patients who underwent surgical chest wall and/or diaphragm repair with decellularized bovine pericardium between January 1, 2012 and January 13, 2022 at our institution. All records were screened for patient characteristics, intra-/postoperative complications, chest tube and analgesic therapy duration, length of hospital stay, presence or absence of redo procedures, as well as morbidity and 30-day mortality. We then looked for correlations between implanted graft size and postoperative complications and gathered further follow-up information at least 2 months after surgery.Results A total of 71 patients either underwent isolated chest wall (n = 51), diaphragm (n = 12), or pericardial (n = 4) resection and reconstruction or a combination thereof. No mortality was recorded within the first 30 days. Major morbidity occurred in 12 patients, comprising secondary respiratory failure requiring bronchoscopy and invasive ventilation in 8 patients and secondary infections and delayed wound healing requiring patch removal in 4 patients. There was no correlation between the extensiveness of the procedure and extubation timing (chi-squared test, p = 0.44) or onset of respiratory failure (p = 0.27).Conclusion A previously demonstrated general viability of biological materials for various reconstructive procedures appears to be supported by our long-term results.
Keywords: chest wall resection; diaphragm resection; biological materials; periguard